Acute myeloid leukaemia therapeutic innovation and clinical trials: past, present and future. (15th November 2020) - Craddock, Charles
Summary: Outcomes in acute myeloid leukaemia have improved steadily over the last six decades thanks to advances in disease classification, risk stratification and the advent of new drug and transplant therapies. Over this period the UK has made a major contribution to this international effort, both through its delivery of large prospective randomised trials with integrated genomic and measurable residual disease assessments and its pioneering role in the development of allogeneic stem cell transplantation as a potent anti‐leukaemic therapy.